Persepsi Siswa terhadap Pembelajaran Sejarah pada Masa Covid-19 pada Siswa Kelas XI IIS SMA Negeri 3 Mukomuko - Suci Anggela; Jaenam Jaenam; Felia Siska (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
This research is motivated by the presence of Covid-19 which has an impact on all fields including education. The purpose of this study was to describe students' perceptions of history learning during the Covid-19 class XI IIS SMA Negeri 3 Mukomuko. The research method used is descriptive qualitative analysis. The research location is in SMA Negeri 3 Mukomuko, Mukomuko district. The data collection techniques in this study were observation, interviews and documentation. The results showed that: 1) Students' perceptions of the history learning method during the Covid-19 period at SMA Negeri 3 Mukomuko were students found it difficult to understand the material with the history learning method used by the teacher during face-to-face meetings. Likewise with online learning, because when learning online, teachers send assignments more often than explain the subject matter. 2) Students' perceptions of History learning media during the Covid-19 period at SMA Negeri 3 Mukomuko were students did not understand the subject matter delivered using the assignment method via cellphone with the Whatsapp platform media. This means that the teacher's efforts in using the History learning method during the Covid-19 period exist, but are not maximized. The teacher uses two media here where Whatsapp is an interactive media and Powerpoint is an audio-visual medium.